2022
DOI: 10.1039/d1ra06753b
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for the preparation of non-amplified and amplified genomic dengue gene samples for electrochemical DNA biosensing applications

Abstract: The application of electrochemical DNA biosensors in real genomic sample detection is challenging due to the existence of complex structures and low genomic concentrations, resulting in inconsistent and low current signals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 77 publications
(80 reference statements)
0
4
0
Order By: Relevance
“…The pH value of 7.5 indicated the highest current peak (ΔI) which resulted in the most hybridization of target OMP-C. The lower signal flow at a lower pH value and higher than 7.5 may be attributed to reduce the accessibility of bound ssDNA probe for hybridization by tensile surface stress due to hydration and electrostatic induced forces 44 , 45 . So, the effect of probe concentrations was investigated by using the SWV technique in a solution buffer at pH = 7.5.…”
Section: Discussionmentioning
confidence: 99%
“…The pH value of 7.5 indicated the highest current peak (ΔI) which resulted in the most hybridization of target OMP-C. The lower signal flow at a lower pH value and higher than 7.5 may be attributed to reduce the accessibility of bound ssDNA probe for hybridization by tensile surface stress due to hydration and electrostatic induced forces 44 , 45 . So, the effect of probe concentrations was investigated by using the SWV technique in a solution buffer at pH = 7.5.…”
Section: Discussionmentioning
confidence: 99%
“…The preparation of genomic dengue virus genes from real samples has been described in our previous work. 4 …”
Section: Methodsmentioning
confidence: 99%
“…Moreover, previous research has demonstrated that electrochemical approaches can achieve femtomolar or attomolar concentrations, which is benecial for the clinical diagnosis of infectious diseases. 1,2 Coupling POC devices with miniaturized electrochemical transducers has transformed the detection landscape, enabling real-time, rapid detection of various infectious diseases, including COVID-19, 3 dengue virus (DENV), 4 Zika virus, 5 Inuenza, 6 Hepatitis, 7 human immunodeciency (HIV), 8 Salmonella 9 and Tuberculosis. 10 Electrochemical biosensors rely on changes in measurable redox current due to specic interactions between immobilized biological recognition elements and analytes, such as ssDNA/RNA-ssDNA, aptamer-antigens/proteins, antibodiesantigens, and whole cells-antigen/proteins.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation